La planificación en el marco de la actualización y fortalecimiento curricular del primer año de educación general básica y su incidencia en el proceso de enseñanza aprendizaje de las niñas y niños del jardín de Infantes José Miguel García Moreno de la ciudad de Loja, paralelos B-C-G, año 2011-2012. Lineamientos alternativos - Lozano Salinas, Luzmila Albertina (2014)
The research problem refers to planning in the framework of the Updating and Strengthening Curriculum First Year of Basic General Education and its impact on the teaching-learning process of the children of the Kindergarten "José Miguel García Moreno" the Loja, parallel B, C, G, 2011-2012. To achieve the same general goal was raised to establish the incidence of planning in the framework of the Updating and Strengthening Curriculum First Year of Basic General Education in the teaching-learning process. The methods used for data collection and data analysis were: Scientist, Inductive, Deductive and description, the same that were used to discover and explain the relationship between the study variables. The techniques and tools that were applied were: survey of teachers to know the characteristics of the planning and observation guide for the documentary study of the leading professional planning for the location within the update and Strengthening Curriculum. Among the conclusions, it can be noted that the characteristics of the planning undertaken by teachers in the First Year of Garden investigated, negative impact on the teaching-learning process whose results can be seen reflected in the grades earned. Planning is not related to the proposal promoted by the Ministry of Education. The teachers in their planning lack the necessary advice and teaching resources, so that perceptions and practices of teachers do not succeed due. No one takes into account the component of coexistence, understanding and artistic expression and the body language and only sometimes considered the initial, motivational, attitudinal and procedural activities.